Ferroptosis is involved in regulating perioperative neurocognitive disorders: emerging perspectives - Yanhong Song; Ziyi Wu; Hang Xue; Ping Zhao (Journal of Neuroinflammation, 2022)
Abstract Since the twenty-first century, the development of technological advances in anesthesia and surgery has brought benefits to human health. However, the adverse neurological effects of perioperative-related factors (e.g., surgical trauma, anesthesia, etc.) as stressors cannot be ignored as well. The nervous system appears to be more “fragile” and vulnerable to damage in developing and aging individuals. Ferroptosis is a novel form of programmed cell death proposed in 2012. In recent years, the regulation of ferroptosis to treat cancer, immune system disorders, and neurodegenerative diseases have seen an unprecedented surge of interest. The association of ferroptosis with perioperative neurocognitive disorders has also received much attention. Cognitive impairment can not only affect the individual’s quality of life, but also impose a burden on the family and society. Therefore, the search for effective preventive and therapeutic methods to alleviate cognitive impairment caused by perioperative-related factors is a challenge that needs to be urgently addressed. In our review, we first briefly describe the connection between iron accumulation in neurons and impairment of brain function during development and aging. It is followed by a review of the pathways of ferroptosis, mainly including iron metabolism, amino acid metabolism, and lipid metabolism pathway. Furthermore, we analyze the connection between ferroptosis and perioperative-related factors. The surgery itself, general anesthetic drugs, and many other relevant factors in the perioperative period may affect neuronal iron homeostasis. Finally, we summarize the experimental evidence for ameliorating developmental and degenerative neurotoxicity by modulating ferroptosis. The suppression of ferroptosis seems to provide the possibility to prevent and improve perioperative neurocognitive impairment.